Creation of neovagina in women with Müllerian agenesis (Mayer-Rokitansky-Küster-Hauser syndrome) using fresh human amnion - Abdulrahim Gari; Saeed Baradwan; Radiah Iskandarani; Ammar Y Alkhiary; Abdulmalik Abumohssin; Ahmed Abu-Zaid (Korean Society of Obstetrics and Gynecology, 2024)
Objective Several graft options can be used to construct a neovagina. This study aimed to evaluate the efficacy of creating a neovagina using a fresh human amnion in women with Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome. Methods Ten patients were analyzed retrospectively. Anatomical success was defined by a postoperative vaginal length ≥5 cm, and a width sufficient to comfortably accommodate the insertion of two fingers. Functional success was achieved when a score of >26.5 was attained on the Arabic validated version of the functional sexual function index (FSFI). Results Overall, the mean vaginal length before surgery was 2.15±0.85 cm (range, 1.5-4.5). The mean vaginal length after surgery was 5.5±0.53 cm (range, 5-6), and all patients (n=10) achieved anatomical success. The FSFI score after surgery was 29.2±2.4, and eight patients achieved functional success. The mean operative time and estimated blood loss were 83.5±50.31 minutes (range, 42-210) and 122.0±75.69 mL (range, 20-250), respectively. None of the patients required intraoperative blood transfusion or experienced injury to vital organs. Four patients developed postoperative leukocytosis within 48 hours, and one patient experienced chronic pelvic pain that lasted more than 6 months postoperatively. No major postoperative complications, such as pelvic abscesses, open wounds, chronic vaginal discharge, or reoperation, were reported. Conclusion In conclusion, surgical dissection of the vesicorectal space and utilization of fresh human amnion to create a neovagina over a vaginal mold are technically feasible and safe, and are linked to favorable anatomical and functional outcomes in MRKH patients with vaginal agenesis.